Withania somnifera phytochemicals confer neuroprotection by inhibition of the catalytic domain of human matrix metalloproteinase-9 - Kumar G.; Paliwal P.; Patnaik R. (My University, 2025)
Background: Matrix metalloproteinase-9 (MMP-9) expression is elevated in neurological diseases, and its up-regulation may exert to the pathogenesis of many neurological disorders. Therefore, inhibition of MMP-9 can be of neuroprotective approach. Objective: The present in silico study carried out to explore the possible neuroprotective potential of Withania somnifera phytochemicals through inhibition of MMP-9. Method: Twenty-seven Withania somnifera phytochemicals were selected for this study based on their BBB penetration ability and suitability for Lipinski's rule of five. Further, molecular docking was performed to know whether these phytochemicals inhibit the MMP-9 or not. Results: The results suggest that 17 phytochemicals have the higher affinity for S1'-specificity pocket of the MMP-9 catalytic domain than two inhibitors reverse hydroxamate and quercetin. Because of they directly bound to the active site with lower binding energy and established some hydrogen bonds and hydrophobic interactions with residues critical in mediating inhibition. Conclusion: These phytochemicals have potential as an intrinsically useful oral drug to combat neurological disorders mediated by MMP-9. © 2017 Bentham Science Publishers.